Understanding the roles of salt-inducible kinases in cardiometabolic disease - Shi, Fubiao (Frontiers in Physiology, 2024)
Salt-inducible kinases (SIKs) are serine/threonine kinases of the adenosine monophosphateactivated protein kinase family. Acting as mediators of a broad array of neuronal and hormonal signaling pathways, SIKs play diverse roles in many physiological and pathological processes. Phosphorylation by the upstream kinase liver kinase B1 is required for SIK activation, while phosphorylation by protein kinase A induces the binding of 14-3-3 protein and leads to SIK inhibition. SIKs are subjected to auto-phosphorylation regulation and their activity can also be modulated by Ca 2+ /calmodulin-dependent protein kinase in response to cellular calcium influx. SIKs regulate the physiological processes through direct phosphorylation on various substrates, which include class IIa histone deacetylases, cAMP-regulated transcriptional coactivators, phosphatase methylesterase-1, among others. Accumulative body of studies have demonstrated that SIKs are important regulators of the cardiovascular system, including early works establishing their roles in sodium sensing and vascular homeostasis and recent progress in pulmonary arterial hypertension and pathological cardiac remodeling. SIKs also regulate inflammation, fibrosis, and metabolic homeostasis, which are essential pathological underpinnings of cardiovascular disease. The development of small molecule SIK inhibitors provides the translational opportunity to explore their potential as therapeutic targets for treating cardiometabolic disease in the future.